(untitled) (Journal of EAHIL, 2018)
Anu Ojaranta, a doctoral student in Åbo Akademi University in Turku Finland discusses her career development and how the path took her to entrepreneurship in the field of Information and Library Science. What does it take to become an entrepreneur, what skills are required and what kind of personal character is needed.